Unraveling the role of dextral faults in the formation of pull-apart basin structures and their implications on the genesis of ophiolites and pluto-volcanics - MohammadiNia, Ali; Rashidi, Ahmad; Shafieibafti, Shahram; Mousavi, Seyed Morteza; Nemati, Majid; Kianimehr, Hossein; Ezati, Maryam; Derakhshani, Reza (Frontiers in Earth Science, 2024)
Rhombic structures have been observed in the Qom-Zefreh-Nayin-Dehsheir-Baft region, specifically along the direction of the dextral faults, which have caused significant changes in strike length. This study investigates the geological features and fault interactions in the region through the examination of aerial images, fault-lithology correlations, petrology, crustal thickness, and seismic studies. The analysis of aerial photos and geological correlations revealed the presence of ophiolites and pluto-volcanics associated with faults and rhombic structures. By conducting field geology and combining various geological studies, a pull-apart basin was identified in the area, contributing to the formation of three rhombic structures. This basin played a crucial role in the genesis of the region's ophiolites and pluto-volcanics. The research suggests that the initial tensional stress leading to the pull-apart basin was caused by the right step of a dextral fault within the Urumieh-Dokhtar magmatic arc. This fault formation occurred due to the oblique Arabian subduction towards the Iranian plateau. During the Zagros orogeny, the stretched area persisted, leading to the formation of oceanic crust in this location. The subduction angle changes from subduction to supersubduction, resulting in the classification of the region into two types: C and E genes. Different types of magma, including alkaline, subalkaline, shoshonite, calcalkaline, and adakitic, were identified in this region. The study highlights the significance of tholeiitic arcs, abyssal features, crust thickness, and seismicity in understanding oblique diagonal subduction models and tensional pull-apart basins, which are crucial in the transition from subduction to super-subduction. This research offers valuable insights into the geological complexities of the region and opens up opportunities for further exploration of similar models.